Abdominal and pelvic adipose tissue distribution and risk of prostate cancer recurrence after radiation therapy. Issue 14 (7th August 2020) - Di Bella, Claire M.; Howard, Lauren E.; Oyekunle, Taofik; De Hoedt, Amanda M.; Salama, Joseph K.; Song, Haijun; Freedland, Stephen J.; Allott, Emma H.
Abstract: Background: Fat distribution varies between individuals of similar body mass index (BMI). We hypothesized that visceral obesity is more strongly associated with poor prostate cancer outcomes than overall obesity defined by BMI. Materials and Methods: We quantified abdominal visceral and subcutaneous fat area (VFA and SFA), and pelvic periprostatic adipose tissue area (PPAT), using computed tomography scans from radiation‐treated prostate cancer patients at the Durham North Carolina Veterans Administration Hospital. Multivariable‐adjusted Cox regression examined associations between each adiposity measure and risk of recurrence, overall and stratified by race and receipt of androgen deprivation therapy (ADT). Results: Of 401 patients (59% black) treated from 2005 to 2011, 84 (21%) experienced recurrence during 9.3 years median follow‐up. Overall, obesity defined by BMI was not associated with recurrence risk overall or stratified by race or ADT, nor was any measure of fat distribution related to the risk of recurrence overall or by race. However, higher VFA was associated with increased risk of recurrence in men who received radiation only (hazard ratio [HR], 1.79; 95% confidence interval [CI], 0.87‐3.66), but inversely associated with recurrence risk in men treated with radiation and ADT (HR, 0.49; 95% CI, 0.24‐1.03; P ‐interaction   = .002), though neither association reached statistical significance. Similar patterns of ADT‐stratified associations were observed for PPAT and SFA. Conclusions: Associations between abdominal and pelvic adiposity measures and recurrence risk differed significantly by ADT receipt, with positive directions of association observed only in men not receiving ADT. If confirmed, our findings suggest that obesity may have varying effects on prostate cancer progression risk dependent on the hormonal state of the individual.